Synthesis of L-tyrosine-capped ZnSe quantum dots and its application to hypochlorite determination in water. Issue 10 (8th August 2016) - Hosseini, Mohammad Saeid; Hashemi-Pour, Zahra; Hosseini, Navid
ABSTRACT: In this study, a new sensitised spectrofluorometric method was presented as a probe sensor for hypochlorite analysis in oral and tap water samples. By capping L-tyrosine (Tyr) on ZnSe nanoparticles, stable quantum dots (QDs) were obtained. In comparison with Tyr, the fluorescence (FL) emission of Tyr-capped ZnSe is enhanced and shifted to greater wavelength, which causes to enhance the sensitivity for the determination of hypochlorite. Based on the FL quenching of the Tyr-capped ZnSe QDs, hypochlorite concentration was detected at buffering pH of 7 in the range of 5.15 × 10 − 5 ‒2.57 × 10 − 2 g L −1 . Relative standard deviation and detection limit were found to be 0.83% and 2.06 × 10 − 5 g L −1, respectively. In comparison with the other methods of hypochlorite determination, this method is simple, fast and inexpensive, with low sample volume consumption. It also exhibits a good selectivity.